Impact of Social Media Usage on Academic Performance of Tertiary Institution Students: Evidence From Accra & Tema Metropolis, Ghana - Asante, Edward; Martey, Edward Markwei (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
The study sought to assess the relationship between student’s use of social media and academic performance of tertiary institutions students in Ghana with a focus on Accra and Tema Metropolis. Questionnaire was used for collecting data. Out of one thousand copies of the questionnaire distributed, a valid response of 70.0 % was retrieved. SPSS computer software was used to measure descriptive, correlation, regression among others. The study revealed that all the constructs of social media (dependent variable) had a significant positive relationship thus the independent variables (Facebook, Whatsapps, Yahoo Messenger, Skype, and Twitter) at level 0.01 with the dependent variable academic performance.